The method of unitary clothing transformations in quantum field theory: the bound-state problem and the S-matrix - Shebeko, A.V. (Вопросы атомной науки и техники, 2007)
Being aimed at reformulating quantum field theory (QFT) within the notion of the so-called clothed particles and interactions between them we consider the problem of finding the simplest eigenstates of the total field Hamiltonian H. Along this guideline H and other operators of great physical meaning, e.g., the Lorentz boost generators and the current density operators, which depend initially on the creation and destruction operators for the “bare” particles, are expressed through a new family of their “clothed” counterparts. We are stressing that this transition to the clothed-particle representation (CPR) has been fulfilled via certain unitary (“clothing”) transformations (UT’s) without changing the original Hamiltonian. It is shown how the S-matrix can be evaluated in the CPR.